2019
DOI: 10.3390/cells8111435
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Stromal Microenvironment Experimental Model Containing Proto-Myofibroblast Like Cells and Analysis of Its Crosstalk with Melanoma Cells: A New Tool to Potentiate and Stabilize Tumor Suppressor Phenotype of Dermal Myofibroblasts

Abstract: Melanoma is one of the most aggressive solid tumors and includes a stromal microenvironment that regulates cancer growth and progression. The components of stromal microenvironment such as fibroblasts, fibroblast aggregates and cancer-associated fibroblasts (CAFs) can differently influence the melanoma growth during its distinct stages. In this work, we have developed and studied a stromal microenvironment model, represented by fibroblasts, proto-myofibroblasts, myofibroblasts and aggregates of inactivated myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…Consistently, several human epidemiologic investigations have confirmed the efficacy of NSAIDs not only in eliciting anti-tumor effects, but also in significantly decreasing the risk of BC [ 244 , 245 , 246 ]. In line with these findings, other compelling studies have reported that suppression of COX-2 expression in primary cutaneous myofibroblasts induces an in vitro anti-tumor phenotype [ 247 , 248 ].…”
Section: Role Of Bcafs In Bc Cell Dissemination and Metastasissupporting
confidence: 70%
“…Consistently, several human epidemiologic investigations have confirmed the efficacy of NSAIDs not only in eliciting anti-tumor effects, but also in significantly decreasing the risk of BC [ 244 , 245 , 246 ]. In line with these findings, other compelling studies have reported that suppression of COX-2 expression in primary cutaneous myofibroblasts induces an in vitro anti-tumor phenotype [ 247 , 248 ].…”
Section: Role Of Bcafs In Bc Cell Dissemination and Metastasissupporting
confidence: 70%
“…The use of NPs for an early and precise identification of cancer cells can help to avoid delayed diagnosis, and the specific delivery of a limited amounts of drug directly to cancer cells can effectively reduce chemotherapyrelated side effects (Parvanian et al, 2017;Zhao et al, 2018;Chen Y. et al, 2019). At the same time, the usage of NPs can be useful to bypass the drug resistance of some tumors, like melanoma (Naves et al, 2017;Avagliano et al, 2019). In this scenario, the surface modification of NPs represents an important strategy to successful develop specific and biocompatible nano-platforms for precise and sensitive therapy and/or diagnosis.…”
Section: The Role Of Nanoparticles In Cancer Diseasementioning
confidence: 99%
“…In fact, it includes ECM molecules, represented by laminin and collagen, growth factors, including VEGF, nutrients, such as glucose, blood and lymphatic tumor vessels, various concentrations of oxygen, cancer and stromal cells, that influence each other to sustain tumor growth, progression and metastasis (9,160,161). Non-cancer stromal cells are represented by endothelial cells, pericytes, immune cells, fibroblasts, fibroblast aggregates, myofibroblasts, cancer associated fibroblasts (CAFs), activated adipocytes, and mesenchymal stem cells (MSCs) (9,(162)(163)(164)(165). In the complex, melanoma microenvironment represents a niche produced and regulated by the bidirectional interactions of melanoma cells with surrounding cells, tumor vessels and ECM (166).…”
Section: Metabolic Crosstalk Between Melanoma Cells and Tmementioning
confidence: 99%
“…Fibroblasts, fibroblast aggregates, myofibroblasts and CAFs represent important constituents of melanoma stromal microenvironment (163,165,168). It is known that normal dermal fibroblasts, before CAF differentiation, hamper melanoma formation at its early stage (169).…”
Section: Metabolic Crosstalk Between Fibroblasts and Melanoma Cellsmentioning
confidence: 99%